Blood gene expression correlated with tic severity in medicated and unmedicated patients with Tourette Syndrome. (December 2010) - Liao, Isaac H; Corbett, Blythe A; Gilbert, Donald L; Bunge, Silvia A; Sharp, Frank R
Background: Tourette Syndrome (TS) has been linked to both genetic and environmental factors. Gene-expression studies provide valuable insight into the causes of TS; however, many studies of gene expression in TS do not account for the effects of medication.Materials & methods: To investigate the effects of medication on gene expression in TS patients, RNA was isolated from the peripheral blood of 20 medicated TS subjects (MED) and 23 unmedicated TS subjects (UNMED), and quantified using whole-genome Affymetrix microarrays.Results: D2 dopamine receptor expression correlated positively with tic severity in MED but not UNMED. GABAA receptor ε subunit expression negatively correlated with tic severity in UNMED but not MED. Phenylethanolamine N -methyltransferase expression positively correlated with tic severity in UNMED but not MED.Conclusion: Modulation of tics by TS medication is associated with changes in dopamine, norepinephrine and GABA pathways.